2021
DOI: 10.1017/s0263574721000746
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and power optimization of a 4RPSP+PS parallel flight simulator machine

Abstract: Reducing consumed power of a robotic machine has an essential role in enhancing its energy efficiency and must be considered during its design process. This paper deals with dynamic modeling and power optimization of a four-degrees-of-freedom flight simulator machine. Simulator cabin of the machine has yaw, pitch, roll and heave motions produced by a 4RPSP+PS parallel manipulator (PM). Using the Euler–Lagrange method, a closed-form dynamic equation is derived for the 4RPSP+PS PM, and its power consumption is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It tends to have higher speed, acceleration, stiffness and payload capacity, lower inertia property, at the cost of limited reachable workspace and many singularity configurations, by comparison with its counterpart serial robot in the similar conditions [1,2]. Parallel manipulators have received increased interest due to their intrinsic advantages and are widely employed in various industrial applications: pick-and-place robots [3,4], flight simulators [5], multi-axis parallel kinematic machine tools [6,7], haptic devices [8] and medical robots [9]. A systematic design of a group of novel parallel architectures is the primary step in robotics.…”
Section: Introductionmentioning
confidence: 99%
“…It tends to have higher speed, acceleration, stiffness and payload capacity, lower inertia property, at the cost of limited reachable workspace and many singularity configurations, by comparison with its counterpart serial robot in the similar conditions [1,2]. Parallel manipulators have received increased interest due to their intrinsic advantages and are widely employed in various industrial applications: pick-and-place robots [3,4], flight simulators [5], multi-axis parallel kinematic machine tools [6,7], haptic devices [8] and medical robots [9]. A systematic design of a group of novel parallel architectures is the primary step in robotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the additional degrees of freedom increase the complexity of the kinematic model and control framework. Zarkandi [15] discusses the problem of dynamic modeling and power optimization for a parallel platform. Han et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the additional degrees of freedom increase the complexity of the kinematic model and control framework. Zarkandi [15] discusses the problem of dynamic modeling and power optimization for a parallel platform. Han et al [16] propose a unified kinematic modeling method for reconfigurable landing and roving probes with full consideration of six-dimensional foot-terrain interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel Manipulators (PMs) have gained a wide attention from the research fraternity due to the numerous advantages they offer over their serial counterparts like higher rigidity, better load carrying capacity, precise positioning, higher payload to weight ratio, higher kinematic and better dynamic features. 1,2 These traits allow the PMs to be used in numerous practical applications like in manufacturing, 3 lifting mechanisms, 4,5 space technologies, 6 simulators, 7,8 friction stir welding machines, 9 etc. In recent decades, it has been found that 3-DoF PMs are relevant to substitute 6-DoF PMs in most of the applications because of their advantages such as lower design and manufacturing cost, as well as a simpler architecture.…”
Section: Introductionmentioning
confidence: 99%